Altitude and temperature drive anuran community assembly in a Neotropical mountain region - Matavelli, Rodrigo [UNESP]; Oliveira, Juliano Machado [UNESP]; Soininen, Janne; Ribeiro, Milton Cezar [UNESP]; Bertoluci, Jaime (Wiley, 2022)
Understanding the spatial variation in species richness and the mechanisms that limit species range sizes along geographical gradients belong to the central research issues in macroecology. Here, we aim to test the topographic and climatic effects on anuran species richness and community composition in mountainous regions in the Brazilian Atlantic Forest biome. We used Individual-Based Rarefaction Curve (interpolation and extrapolation), Generalized Additive Model (GAM), Midpoint method and Principal Coordinates Analysis (PCoA) to analyze the topographic and climatic effects on anuran community composition, richness, and range sizes in a global biodiversity hotspot. Our results showed that altitude and annual mean temperature and temperature seasonality were the main drivers of species altitudinal range sizes and community assembly in mountainous regions. In conclusion, Anuran community richness peaked at intermediate altitudes following thus a hump-shaped pattern and corroborated the Rapoport's altitudinal rule as range sizes increased with altitude in mountainous regions from the Atlantic Forest biome. This study revealed new insights into the patterns and drivers of Neotropical anuran communities. Abstract in Portuguese is available with online material.
Keywords: amphibians; atlantic forest; biodiversity hotspots; neotropical region; Poços de Caldas Plateau; range size; rapoport altitudinal rule